Influência do teor metálico na isomerização do n-hexano sobre Ni-Pt/HUSY - Yoshioka, Carlos Minoru Nascimento (2003)
The isomerization of linear alcanes has arised great interest in the industry of refining of oil with the intention to transform n-paraffins (particularly with 6 and 7 carbon atoms), in iso-paraffins, since these last ones possess high index of octane number, thus improving the efficiency of the automotives engines. The great part of literature works involves the job of bifunctional catalysts that possess acid sites and hydrogenants/deshydrogenants sites. Most of the studies with the bimetallic catalysts was carried through the constant mass, what it can take the maken a mistake interpretations, in function of that, in the case of the pair Pt-Ni, the atomic weight of both metals is very different (195,09 versus 58,71). Thus being, the objective of this work is to verify the influence of the Pt in the reduction and the properties of catalysts formed for Ni+2 supported in zeolite HUSY comparing, however, catalysts that contain a constant atomic metal. In this work, catalysts monometallic bifunctional had been prepared using supported Ni or Pt in zeolite HUSY, and bimetallic contend different ratios of Ni- Pt. The addition of metals in the solid were carried through competitive ion exchange, using solutions of [Ni(NH3)6]Cl2 and [Pt(NH3)4]Cl2. Three series of catalysts had been prepared: first with the total amount of atoms of 30.10-6 atg Me/gcat, second with 130.10-6 atg Me/gcat and third with 180.10-6 atg Me/gcat. The catalysts had been characterized by RTP (reduction the temperature programmed) and submitted to the catalytic evaluation in the isomerization of the n-hexane 250°C and 1 atm in an atmosphere contend a ratio H2/C6 = 9. In the RTP results, a larger reducibility of cations Ni+2 was verified when in presence of Pt, evidenced for the displacement of the peak of reduction in the monometallic catalysts front to the bimetallic. It is possible to observed also, that it has a reduction of the temperatures of reduction with the increase of Pt, indicating a lesser interaction of this metal with the support. In the isomerization reaction, a fast deactivation for the catalysts was observed only contends Ni. The bimetallic catalysts, when compared with the catalysts of Ni, they present a lower deactivation and a great final activity during 6 h reaction. The catalysts which have only Pt, compared to those catalysts which have only Ni, presented greater activity and minimal deactivation. Comparing the bimetallic catalysts with the monometallic, it was observed that catalytic bimetallic with more of 70% of Ni (9.10-6 atg of Ni) they are more active than the monometallic ones (only Pt or Ni). Evaluating it activity in function of the content of Pt, it is observed a maximum for lower content of Pt. Above of this content, an addition of Pt leads to the reduction of the initial catalytic activity.